DESIGN OF TIME CONTROL IN GENERAL LIGHTING ROAD TO IMPROVE EFFICIENCY ELECTRICITY ENERGY BASED ON MICROCONTROLLER ATMEGA 328P - Budi Prastyo; Dody Wahjudi (Teodolita ( Media Komunikasi Ilmiah di Bidang Teknik ), 2019)
One technology that needs to improve efficiency is the Public Street Lighting (PJU) system. PublicStreet Lighting System (PJU) with automatic control using a light switch (photocell) has not been able toreduce the waste of electrical energy. So it is necessary to have a time controller that can be used aselectrical energy efficiency on public street lighting. For this reason, it is necessary to design an atmega328p microcontroller-based time controller that is biased as well as to conduct electrical energy efficiency.This tool has advantages over the others is resistant to moisture, dust, the risk of insect entry. Equipped withRTC DS3231 with very small time shifts. Easy installation process. Equipped with an LCD to monitor.Equipped with a menu / button control buttons for the process of operating settings. Increases the efficiencyof electrical energy. Improve the efficiency of operational costs for maintenance or maintenance.Keyword : Timer, Microcontroller, EfficiencyABSTRAKSalah satu teknologi yang perlu peningkatan efisiensi adalah sistem Penerangan Jalan Umum (PJU).Sistem Penerangan Jalan Umum (PJU) dengan kendali otomatis menggunakan saklar cahaya (photocell)belum mampu mengurangi pemborosan energi listrik. Sehingga perlu adanya suatu pengendali waktu yangbias digunakan sebagai efisiensi energi listrik pada penerangan jalan umum. Untuk itu perlu dirancangpengendali waktu berbasis mikrokontroler atmega 328p yang bias sekaligus untuk melakukan effisiensienergy listrik. Alat ini mempunyai keunggulan dibanding yang lain adalah Tahan terhadap kelembapan,debu, resiko masuknya serangga. Dilengkapi dengan RTC DS3231 dengan pergesaran waktu yang sangatkecil. Mudah dalam proses pemasangan. Dilengkapi dengan LCD untuk memonitor.Dilengkapi dengantombolk kontrol menu/pilihan untuk proses pengaturan operasi.Meningkatkan efisensi energi listrik.Meningkatkan efisiensi biaya operasional pemeliharaan atau perawatan.Kata kunci : waktu, mikrokontroller, effisiensi